Development Of Quality Measurement Of Cooperative Governance Implementation - Devid Putra Arda; Etty Murwaningsari; Juniati Gunawan (International Journal of Science, Technology & Management, 2021)
According to the Constitution of the Republic of Indonesia, Article 33 of the 1945 Constitution, the basis for the establishment of cooperatives in Indonesia, is intended to be one of the solid pillars of the nation's economy. Cooperatives have not played much role in reducing people's poverty and realizing food independence (Tjakrawerdjaja, 2019). The purpose of this study is to develop a measurement of the quality of the implementation of cooperative governance. Cooperative governance that is not based on the principle of good cooperative governance has the potential to have a negative impact on the health of cooperatives and the survival of cooperatives (Budiyono & Susilowati, 2017). The research method used in this study is qualitative research, which emphasizes analyzing and interpreting a problem (Afrizal, 2014). Participants in this study are those who have knowledge and experience about cooperatives. The population will spread across the scope of the cooperative, especially at the level of administrators, supervisors, and management. The process of analyzing research data is carried out inductively, namely data analysis is carried out simultaneously with data collection in a cyclical process (Nugrahani, 2014). The data analysis model that the author uses is the interactive analysis of Miles & Huberman. In order to collect data from information sources or informants, researchers need assistance instruments that are used semi-structured interview guidelines. The next stage of this research is to conduct content analysis. The main purpose of content analysis is to support answers to research questions, namely the extent to which cooperative governance is implemented. Content analysis is carried out on the Accountability Report of the Cooperative Management and Supervisory Board. The results of this study indicate that the Development of Quality Measurement of Cooperative Governance Implementation, produces 15 (fifteen) dimensions and 97 (ninety-seven) indicators. The level of implementation of the development of measurement of the quality of the implementation of cooperative governance in the two samples of cooperatives obtained the findings: (a) BPK RI Cooperatives received the predicate "not good"; (b) KSP SMS implementation level gets the predicate “Good”.